2007
DOI: 10.5034/inquiryjrnl_44.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Public Reporting and Pay-for-Performance: Safety-Net Hospital Executives' Concerns and Policy Suggestions

Abstract: Safety-net hospitals (SNHs) may gain little financial benefit from the rapidly spreading adoption of public reporting and pay-for-performance, but may feel compelled to participate (and bear the costs of data collection) to meet public expectations of transparency and accountability. To better understand the concerns that SNH administrators have regarding public reporting and pay-for-performance, we interviewed 37 executives at randomly selected California SNHs. The main concerns noted by SNH executives were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…See Table 3 [61,74,76,77,79]. More specifically, implementation requires the organization to be fully committed to, and supportive of, the chosen funding model, recognizing it as a strategy to improve quality [71,74,76,77]. Implementation success of P4P also requires the necessary infrastructure to support the individuals and activities required to accurately measure quality [61,74,77].…”
Section: Thematic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…See Table 3 [61,74,76,77,79]. More specifically, implementation requires the organization to be fully committed to, and supportive of, the chosen funding model, recognizing it as a strategy to improve quality [71,74,76,77]. Implementation success of P4P also requires the necessary infrastructure to support the individuals and activities required to accurately measure quality [61,74,77].…”
Section: Thematic Resultsmentioning
confidence: 99%
“…Several themes emerged from the data, each describing leaders' perspectives and/or experiences of implementing ABF or P4P in inpatient hospital settings: (1) pre-requisites for success, (2) perceived benefits, (3) barriers/challenges, (4) unintended consequences, and (5) leader recommendations. See Table 3 [61,74,76,77,79]. More specifically, implementation requires the organization to be fully committed to, and supportive of, the chosen funding model, recognizing it as a strategy to improve quality [71,74,76,77].…”
Section: Thematic Resultsmentioning
confidence: 99%
“…The last component to take into consideration is the additional costs (i.e., cost for pay for reporting) because they can be a burden to healthcare organizations financially. In relation to this matter, Goldman et al indicated that government or health plan should support to gather quality data and should pay for additional costs or reduce the costs for data collection [26]. Overall, to allow a smoother and successful expansion of the VIP for hospitals and clinics, HIRA could to take into the consideration of volunteer participation and financial incentives without penalties in the early stages of the VIP.…”
Section: Discussionmentioning
confidence: 96%
“…24,25 It would be surprising if the observed improvements came without financial cost. To our knowledge, this is the first published study to examine the relationship between alternative definitions of "performance" and the distribution of winners and losers.…”
Section: Borden and Blusteinmentioning
confidence: 99%